Presence/Absence and Specific Location of Resident CD34+ Stromal Cells/Telocytes Condition Stromal Cell Development in Repair and Tumors - Díaz-Flores, Lucio; Gutiérrez, Ricardo; García, Ma Pino; González-Gómez, Miriam; Díaz-Flores, Lucio; Álvarez-Argüelles, Hugo; Luis Carrasco, José (Frontiers in Cell and Developmental Biology, 2020)
CD34+ stromal cells/telocytes (CD34+SCs/TCs) can have a role as mesenchymal precursor cells. Our objective is to assess whether the myofibroblastic stromal cell response in repair and in desmoplastic reactions in tumours depend on the presence or absence of resident CD34+SCs/TCs in specific regions/layers of an organ and on the location of their possible subpopulations. For this purpose, using conventional and immunohistochemical procedures, we studied specimens of a) acute cholecystitis, with early repair phenomena (n: 6), b) surgically resected segments of colon tattooed with India ink during previous endoscopic removal of malignant polyps, with macrophage infiltration and stromal cell reaction (n: 8) and c) infiltrative adenocarcinomas of colon, with desmoplastic reaction (n: 8). The results demonstrated a) stromal myofibroblastic reaction during repair and tumour desmoplasia in most regions in which resident CD34+SCs/TCs are present, b) absence of stromal myofibroblastic reaction during repair in the mucosa of both organs in which resident CD34+SCs/TCs are absent and c) permanence of CD34+SCs/TCs as such, without myofibroblastic response, in smooth muscle fascicles, nerves, and Meissner and Auerbach plexuses, in which the CD34+SCs/TCs mainly undergo reactive phenomena. Therefore, the development of activated αSMA+ myofibroblasts in these conditions requires the presence of resident CD34+SCs/TCs and depends on their location. In conclusion, the facts support the hypotheses that CD34+SCs/TCs participate in the origin of myofibroblasts during repair and tumour stroma formation, and that there is a heterogeneous population of resident CD34+SCs/TCs with different roles.